2002
DOI: 10.1248/bpb.25.1432
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Analgesic, Anti-inflammatory and Antibacterial Activities of Some Novel 2-Phenyl-3-substituted Quinazolin-4(3H) Ones.

Abstract: A series of novel 2-phenyl-3-substituted quinazolin-4(3H)-ones have been synthesized by treating methyl-N-(2-phenyl quinazolin-3-yl-4(3H)-one) dithiocarbamate with different amines, the starting material dithiocarbamate was synthesized from anthranilic acid. The title compounds were investigated for analgesic, anti-inflammatory and antibacterial activities. All the test compounds exhibited significant activity, the compounds A1, A2 and A3 shown more potent analgesic activity, and the compound A3 shown more pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 3 publications
0
57
0
Order By: Relevance
“…Quinazolines and condensed quinazolines exhibit potent antimicrobial 1) and central nervous system (CNS) activities like analgesic, 2) anti-inflammatory 3) and anticonvulsant 4) activities. In view of these facts and to develop our earlier reported 2-phenyl-3-substituted quinazolines, 5) 2,3-disubstituted quinazolines, 6) 2-methyl-3-substituted quinazolin-4-(3H)-ones 7) and 2-methylthio-3-substituted quinazolin-4-(3H)-ones 8) that exhibited good analgesic and anti-inflammatory activities, in the present study we aimed to synthesize some 2-butyl-3-substituted quinazolin-4(3H)-ones. The title compounds were synthesized by nucleophilic substitution of (2-butyl-4-oxo-3H-quinazolin-3-yl)dithiocarbamic acid methyl ester with different amines.…”
mentioning
confidence: 84%
“…Quinazolines and condensed quinazolines exhibit potent antimicrobial 1) and central nervous system (CNS) activities like analgesic, 2) anti-inflammatory 3) and anticonvulsant 4) activities. In view of these facts and to develop our earlier reported 2-phenyl-3-substituted quinazolines, 5) 2,3-disubstituted quinazolines, 6) 2-methyl-3-substituted quinazolin-4-(3H)-ones 7) and 2-methylthio-3-substituted quinazolin-4-(3H)-ones 8) that exhibited good analgesic and anti-inflammatory activities, in the present study we aimed to synthesize some 2-butyl-3-substituted quinazolin-4(3H)-ones. The title compounds were synthesized by nucleophilic substitution of (2-butyl-4-oxo-3H-quinazolin-3-yl)dithiocarbamic acid methyl ester with different amines.…”
mentioning
confidence: 84%
“…In our earlier studies [10][11][12][13] we observed that the presence of alkyl groups exhibited more analgesic and anti-inflammatory activities over aryl groups at the N-3 position. Hence in the C-2 position also we made a substitution in such a way to increase lipophilicity of the molecule.…”
Section: Discussionmentioning
confidence: 89%
“…6) Quinazolin-4(3H)-ones with 2,3-disubstitution is reported to possess significant analgesic, anti-inflammatory 7,8) and anticonvulsant activities. 9) Earlier we have documented 2-phenyl-3-substituted quinazolines, 10) 2-methyl-3-substituted quinazolines, 11) 2-methylthio-3-substituted quinazolines, 12) 2,3-disubstituted quinazolines 13) they exhibited good analgesic and anti-inflammatory activities. The present work is an extension of our ongoing efforts towards the development and identification of new molecules for analgesic and anti-inflammatory activities with minimal gastrointestinal ulceration side effects.…”
mentioning
confidence: 99%
“…Thus, anthranilic acid was treated with benzoyl chloride in the presence of pyridine to undergo cyclization forming 2-phenyl-4H-benzo [d] [1,3]oxazin-4-one (1), which on condensation with hydrazine hydrate yielded 3-amino-2-phenylquinazolin-4(3H)-one (2). The syntheses of the compounds 1 and 2 have been reported by earlier authors [15]. Compound 2 was then treated with different substituted benzaldehydes in the presence of ethanol to form the corresponding 3-(arylideneamino)-2-phenylquinazolin-4(3H)-ones 3a-j.…”
Section: Synthesis Of 3-(arylideneamino)-2-phenylquinazolin-4(3h)-onementioning
confidence: 99%